Design of on-chip temperature-based digital signal processing for customized wireless microcontroller - S.F. R. Faezal; M. N. Isa; S. Taking; S. N. Mohyar; A. B. Jambek; A. Harun (Institute of Advanced Engineering and Science, 2019)
Dramatic rises in power density and die sizes inside system-on-chip (SoC) design have led to the thermal issue. High temperatures or uneven temperature distributions may result not only in reliability issues, also has become the biggest issue that can limit the system performance. This paper presents the design and simulation of a temperature-based digital signal processing unit for modern system-on-chip design using the Verilog HDL. This design provides continuous monitoring of temperature and reacts to specified conditions. The simulation of the system has been done on Synopsys Software. The result showed that temperature monitoring process is within the temperature range due to the incorporation of an interrupt-based system and with an advantage of minimum chip area required.